Human leptospirosis in the Mekong delta, Viet Nam. - Van, C; Thuy, N; San, N; Hien, T; Baranton, G; Perolat, P (1998)
To estimate the seroprevalence of human leptospirosis in the Mekong delta in Viet Nam, an epidemiological survey was conducted in the province of Tien Giang, which is representative of the socioeconomic activities of the region (rice growing and cattle breeding). A cross-sectional study included 35 clusters representing 1400 people randomly selected and aged 15-60 years. Sex, age, occupation, contact with animals, type of water supply, and individual habits were recorded. Leptospiral agglutinins were detected by the microagglutination test, with a battery of 22 live antigens representing the main pathogenic serogroups of Leptospira species and additional local strains. 263 sera (18.8%) gave positive results and 41 (2.9%) had a titre of agglutinins > or = 400, suggesting recent infection. No significant difference was found between females and males. The distribution of seroprevalence was homogeneous throughout the population studied, with the exception of the 15-25 years age group, in which leptospiral antibodies were less frequent. Fifteen serogroups were found, the most prevalent being Bataviae (21.7%), Panama (15.2%), Icterohaemorrhagiae (13.7%) and Australis (8.7%). No significant link between leptospiral seropositivity and professional activities or contacts with animals was found, indicating that leptospirosis in the Mekong delta may be considered as an environmentally linked disease. Leptospirosis is known to be endemic in south-east Asia, and these data demonstrated the high level of circulation of leptospires and the potential importance of leptospiral infections among the rural population in this area.